Подскажите как решение примеров .
(-10)-517=
463-(-39)=
572-(-200)=
(-461)-(-2)=
608-(-909)=
374-(351)=
(-749)-(-69)=
(-663)-(-73)=
835-(240)=
(-668)-405=
(-846)-(-528)=
376-(-858)=
(-582)-130=
(-896)-(501)=
(-271)-855=
7-(66)=
542-(-270)=
(-473)-980=
949-(-325)=
(182)-(-315)=
(-365)-(-589)=
(-83)-291=
(-791)-690=
(-790)-(-144)=
522-(-3)=
(-316)-(-816)=
666- (-526)=
426-(588)=
744-(-288)=
(-374)-574=
(-248)-958=
(-486)-(-743)=
(-526)-988=
(-515)-(97)=
(-500)-887=
(-875)-646=
503-(-22)=
649-(-889)=
(-198)-(-198)=
(-938)-728=
491-(-10)=
(-306)-(-426)=
563-(900)=
500-(-233)=
156-(-813)=
(-912)-738=
(-867)-(-440)=
(-194)-696=
401-(-875)=
(-137)-359=
(-665)-(680)=
(-147)-820=














1

Ответы и объяснения

2014-03-08T17:17:10+04:00
Минус на минус дает + к примеру: 25-(-25) = 25+25 = 50
а -25 - 25 = -50 так же и с твоими примерами